2017
DOI: 10.1242/jeb.151522
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum favors the early emergence of fit and fertile adult Drosophila upon chronic undernutrition

Abstract: Animals are naturally surrounded by a variety of microorganisms with which they constantly interact. Among these microbes, some live in close association with a host and form its microbiota. These communities are being extensively studied, owing to their contributions to shaping various aspects of animal physiology. One of these commensal species, Lactobacillus plantarum, and in particular the L.p.WJL strain, has been shown to promote the growth of Drosophila larvae upon nutrient scarcity, allowing earlier met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 44 publications
(62 reference statements)
2
43
2
Order By: Relevance
“…Irrespective of the means used to generate GF flies, we found that Lp significantly shortened the lifespan of adult Drosophila (Figure 2C, E). These observations match a recent report that GF adults outlive flies mono-associated with the WJL strain of Lp (48) and indicate that mono-association of adults with Lp reverts the extended lifespan noted in GF flies. In contrast, mono-association of adult Drosophila with Ap had no effect on adult lifespan regardless of the method used to generate GF flies ( Figure 2D, F).…”
Section: Mono-association With Lactobacillus Plantarum Shortens Adultsupporting
confidence: 91%
See 1 more Smart Citation
“…Irrespective of the means used to generate GF flies, we found that Lp significantly shortened the lifespan of adult Drosophila (Figure 2C, E). These observations match a recent report that GF adults outlive flies mono-associated with the WJL strain of Lp (48) and indicate that mono-association of adults with Lp reverts the extended lifespan noted in GF flies. In contrast, mono-association of adult Drosophila with Ap had no effect on adult lifespan regardless of the method used to generate GF flies ( Figure 2D, F).…”
Section: Mono-association With Lactobacillus Plantarum Shortens Adultsupporting
confidence: 91%
“…In this report, we used the Drosophila model to examine the effects of symbiotic bacteria on the long-term maintenance of the epithelial renewal program. A recent report showed that mono-association with Lp is not deleterious for adult fly fitness, and has benefits for males raised under conditions of nutrient scarcity (48). In this study, we asked if Lp affects ISC division independent of effects on lifespan, as we showed previously that manipulation of ISC division rates does not have substantial effects on lifespan (36).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to physical differences between laboratory medium and fresh fruit, the nature and concentration of available nutrient are likely to differ. It is well known that lactic and acetic acid bacteria, two taxa that were not investigated in our experiment, can promote larval growth upon nutrient scarcity (Shin et al 2011;Storelli et al 2011, Téfit et al 2017). However, it is also well established that bacteria can affect Drosophila phenotype through signaling (Storelli et al 2011) as well as nutrient provisioning (Brownlie et al 2009;Bing et al 2018;Sannino et al 2018).…”
Section: Different Symbiont Effects In Different Environmentsmentioning
confidence: 88%
“…In this species, bacterial symbionts contribute to a broad range of functions including resource acquisition, digestion, immunity and behavior (Broderick and Lemaitre 2012;Ankrah and Douglas 2018;Schretter et al 2018). Several laboratory studies have established fly nutrition relies on interactions with gut bacteria (Shin et al 2011;Storelli et al 2011;Ridley et al 2012;Wong et al 2014;Huang et al 2015;Leitão-Gonçalves et al 2017;Téfit et al 2017). In particular, bacterial genera frequently associated with laboratory flies, such as Acetobacter and Lactobacillus, can improve larval growth and development when laboratory food is poor in proteins (Shin et al 2011;Storelli et al 2011;Téfit et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation